Teneligliptin inhibits IL‐1β‐induced degradation of extracellular matrix in human chondrocytes. Issue 11 (11th March 2020) - Gao, Feng; Wang, Yanbing; Wu, Minfei
Abstract: The mechanisms driving the pathologic progression of osteoarthritis (OA) have not yet to be fully elucidated. Excessive and irreversible breakdown of the extracellular matrix is the main hallmark of OA. Inhibitors of DPP‐4 have been widely used for over a decade as a treatment for type‐2 diabetes, but the promising function of DPP‐4 inhibitors in chronic inflammatory diseases has only begun to receive attention. Here, we treated human chondrocytes with interleukin‐1β (IL‐1β) with or without teneligliptin to assess the role of DPP‐4 in the enzyme‐driven reduction of type II collagen. Treatment with teneligliptin significantly reduced IL‐1β‐induced expression of tumor necrosis factor α, IL‐6, and IL‐8, generation of reactive oxygen species, increase in metalloproteinase 3 (MMP‐3) and MMP‐13, reduction of tissue inhibitors of matrix metalloproteinase 1 (TIMP‐1) and TIMP‐2, release of lactate dehydrogenase, and activation of the mitogen‐activated protein kinase p38 and nuclear factor κB intracellular signaling pathways, among other things. These findings demonstrate that treatment with teneligliptin may act as a novel therapy to slow or halt disease progression in patients with OA.